2017
DOI: 10.1007/s10900-017-0316-9
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Screening Barriers and Risk Factor Knowledge Among Uninsured Women

Abstract: A steady decline in cervical cancer incidence and mortality in the United States has been attributed to increased uptake of cervical cancer screening tests such as Papanicolau (Pap) tests. However, disparities in Pap test compliance exist, and may be due in part to perceived barriers or lack of knowledge about risk factors for cervical cancer. This study aimed to assess correlates of cervical cancer risk factor knowledge and examine socio-demographic predictors of self-reported barriers to screening among a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
2
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(162 citation statements)
references
References 32 publications
12
141
2
7
Order By: Relevance
“…Previous studies examining factors affecting cervical cancer screening have been conducted in select populations, mainly immigrants and uninsured women in the United States. 30,31 This study provides data on a general population of cervical cancer survivors in three states that could be used to guide interventions to increase cervical cancer screening.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies examining factors affecting cervical cancer screening have been conducted in select populations, mainly immigrants and uninsured women in the United States. 30,31 This study provides data on a general population of cervical cancer survivors in three states that could be used to guide interventions to increase cervical cancer screening.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that, in countries with established screening programs, lower socioeconomic groups or people with particular cultural factors have a much lower screening uptake than the national average, even when screening is provided free of charge. Such groups include ethnic minorities, those living in rural areas, and women on low incomes [ 8 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this public health practice is uncommon, especially in low-income countries, with the lowest adhesion reported in Bhutan (6%) [ 7 ]. In high-income countries with established and free of charge screening programs, there is an increased level of Pap test adherence although people from lower socioeconomic backgrounds have a much lower screening uptake than the national average [ 8 , 9 ]. In Italy, Pap testing was performed free of charge with a coverage in 2017 of at least 80% among resident people [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with low socioeconomic status (SES) or identify as minority, including racial and ethnic underserved minorities such as Hispanics and African Americans, and the LGBTQ (lesbian, gay, bisexual, transgender, and queer or questioning) sexual and gender minorities. It is important to recognize that there is a huge overlap between patients with low SES and those with minority status—rather than face the double impact of being poor and disenfranchised (eg, heightened risks for cancer) [ 84 , 86 - 88 ], as a result of COVID-19, they now face the additional impact of the need to pay extra attention and allocate already limited resources to protect themselves against the coronavirus while also tackling unemployment or hazardous working conditions [ 89 - 91 ].…”
Section: Cancer Screening For At-risk Patient Populationsmentioning
confidence: 99%